Assessment of Undergraduate Research Experience in Term of Benefits, Barriers and Mentorship from Student's Perspectives: A Mixed Quantitative-Qualitative Method - Abdoallah Ahmed, Hayat (International Journal of Medical Students, 2023)
Background Undergraduate research has many demonstrated benefits like enhancement of student’s critical thinking, understanding of research process, and soft skills development, yet so many challenges are facing medical students with availability of time being the most cited among many undergraduates. The aim of this study was to assess the undergraduates research experience in terms of benefits, barriers and mentorship from students perspectives. Methods This study used a mixed quantitative-qualitative approach. The quantitative part was observational, analytical cross-sectional study design with census sampling and 900 participants from 3 batches. The qualitative part constructed in 6 focus group discussions with thematic analysis. The data were collected using standardized pre-validated questionnaire for the quantitative data, and structured questions for the qualitative data. Statistical analysis for the quantitative data was performed using Statistical Package for Social Science (SPSS) ® version No. 26, while qualitative data were analyzed using ATLAS.ti 9 software. Results From 950 census of the three batches, 900 student filled the questionnaire with 94.7% response rate. The mean age of the participants was 24.7, with 69 % females. After finishing their research only 7.7% published their work (65.3% journal, 16.7% conferences presentations). The highest gains reported from this experience were understanding the research process in the medical field, learning to work independently, and ability to read and understand primary literature, while the lowest were learning laboratory techniques, clarification of career path, and confidence in their potential to be science teachers. Themes generated from the qualitative data regarding undergraduate research benefits were: 1. Research knowledge, 2. Soft skills and 3. Scientific/Academic paradigm. The three most reported barriers were research knowledge and skills (44.4%), mentorship (24.4%), and time management (21.7%). When assessing mentorship, 28.9% indicated that their supervisor was about average “He was very good, He wasn't always available, but when available he tries to give us everything he can, generally he was so nice” group3, participant4, 15.8% said he/she is outstanding as a teacher and mentor “she was so supportive (supportive as a supervisor, teacher and even as a mom), she was trying to get the best out of us “ group1, participant1. We investigated the association between students evaluation of their supervisors and their evaluation of the overall research experience, these two variables were moderately correlated (r=.31 , P = .000). Also there is a significant positive correlation between supervisor`s evaluation and students tendency to choose another research experience as undergraduates (r= .2 , P= .000). Nevertheless, Supervisor`s evaluation also correlate with the overall benefits from the research experience (r= .2 , P =.000). Conclusion Undergraduate research experiences had many well-established benefits yet so many challenges were encountered by students when conducting medical researches. These challenges need to be addressed properly in order to maximize the outcomes. Nevertheless, Mentorship is a defining feature and can determine the outcome of the whole research experience among undergraduates, and this necessitate baying further attention to this factor.